2007
DOI: 10.1111/j.1365-2929.2006.02692.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing professionalism in the context of an objective structured clinical examination: an in-depth study of the rating process

Abstract: This study highlights the complexity of the processes involved in assigning ratings to doctor-patient encounters. Greater emphasis on behavioural definitions of specific behaviours may not be a sufficient solution, as raters appear to vary in both attention to and evaluation of behaviours. Reliance on global ratings is also problematic, especially if relatively few raters are used, for similar reasons. We propose a model highlighting the multiple points where raters viewing the same encounter may diverge, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
1
48
0
2
Order By: Relevance
“…Crossley and Jolly (2012) suggested that raters can disagree on the interpretation of a rating scale, even when they agree on their observations. Furthermore, raters of a similar background can focus on different aspects of an interview they are watching, with contrasting results (Mazor et al 2007). Mazor et al (2007), in their study of assessment of medical students' professionalism in an OSCE situation, found that different raters evaluated professionalism by considering a range of contrasting behaviours, resulting in diverse rating outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crossley and Jolly (2012) suggested that raters can disagree on the interpretation of a rating scale, even when they agree on their observations. Furthermore, raters of a similar background can focus on different aspects of an interview they are watching, with contrasting results (Mazor et al 2007). Mazor et al (2007), in their study of assessment of medical students' professionalism in an OSCE situation, found that different raters evaluated professionalism by considering a range of contrasting behaviours, resulting in diverse rating outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, raters of a similar background can focus on different aspects of an interview they are watching, with contrasting results (Mazor et al 2007). Mazor et al (2007), in their study of assessment of medical students' professionalism in an OSCE situation, found that different raters evaluated professionalism by considering a range of contrasting behaviours, resulting in diverse rating outcomes. In the current study, shared discussion about both the scale and the observations therefore may be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…35 This R-squared value was acceptable as Pell et al 35 suggests that correlations of greater than 0.5 indicate a good relationship. In accounting for the remaining variance of 12%, assessors may be using their own professional judgement biases to make their global rating decision 44 and/or making a judgement relative to other students at the same level of training. 29 These are entirely acceptable results as examiners are used on the basis of their professional background and competency.…”
mentioning
confidence: 99%
“…Nos casos clínicos contidos em cada estação, diversas temáticas podem ser exploradas, como executar um procedimento (anotações breves sobre história da doença atual, achados no exame físico, conduta terapêutica, por exemplo), dar ao paciente uma notícia ruim, observar o comportamento perante diferenças culturais, postura ética e até a linguagem no atendimento do paciente 1,9 . O Osce é parte integrante do processo avaliativo de muitos programas de residência médica no exterior e de exames de certificação profissional 10,11 .…”
Section: This Study Aimed To Report the Experience With Objective Strunclassified